THE INFLUENCE OF SOCIAL MEDIA MARKETING AND FINANCIAL LITERACY ON PURCHASE DECISIONS OF GOLD SAVINGS IN PEGADAIAN UNIT BOJA - Marsaa Putri Maharani; Sandi Supaya; Jati Nugroho (Politeknik Negeri Semarang, 2023)
To specify the influence of Social Media Marketing and Financial Literacy on Purchase Decisions is the goals of this research. The issue in this research is due to the expansion of internet users in Indonesia, yet the level of financial literacy in Indonesia is still relatively low and many people don’t know the benefits of Pegadaian’s gold savings product. This study uses quantitive research methods with non-probability sampling techniques (purposive sampling). This study determines the quantity of samples taken are 95 respondents. Multiple linear regression analysis techniques are used to analyze the data in this research, this was held to measure the influence of the independent variables on the dependent variable. The results found that Social Media Marketing and Financial Literacy have significant effect towards Purchase Decisions. The amount of the coefficient of determination is 90,5% on purchase decisions and the remaining 9,5% is influenced by additional factors not considered in this study. This shows that the Social Media Marketing variable and Financial Literacy variable have an important role in increasing the Purchase Decision of gold savings. Based on these data, it is hoped that PT Pegadaian UPC Boja would improve social media marketing and financial literacy so that the decision to purchase gold savings can be achieved.